Estilos de aprendizaje en los estudiantes del quinto nivel carrera profesional de educación inicial facultad de ciencias de la educación y humanidades UNAP 2022 - Rosales Ocampo, Celeste Sther (2023)
The general objective of the research was to describe the learning styles of the students of the fifth level of the professional career of Initial Education, Faculty of Education Sciences and Humanities - UNAP 2021. The type of research with which they worked was non-experimental, each one of the dimensions of the variable learning styles was described, with a Simple Descriptive design, with a population of 193 students of Initial education and a sample of 94 students of the Fifth level, the technique that was used was the survey and as an instrument the Honey-Alonso Scale of 80 items. The global result of the learning styles according to the four dimensions in students of the fifth level of the professional career of Initial Education, 84.4% (27) qualified with a high level of learning style, while 15.6 % (5) qualified with a normal level.